Relationship between social support, impression management and well-being among flood victims in Malaysia - Mustaffa, Che Su; Ahmad Marzuki, Najib; Ariffin, Mohd Taib; Salleh, Nurul ‘Aaina; Rahaman, Nur Haffiza (Elsevier Ltd., 2014)
The purpose of this paper is to discuss the relationship between social support and impression management on the well-being of flood victims in Malaysia.Literature review so far shows that there is a limited research on these variables especially in the area of disaster management in Malaysia. The paper is based on a quantitative approach by conducting a survey among flood victims.This study provides theoretical contributions to organizational communication research and the literature on disaster management context.On the other hand, the findings provide support for the effects of relationships between social support and impression management on the well-being of flood victims.